Spectral cytometry of rheumatoid arthritis patients implicates myeloid dendritic cells and granular HLA-DR+CD15+CD16+ cells in pro-inflammatory antigen presentation - Christian Geier; Haani Qudsi; Estelle Khairallah; Jihad Ben Gabr; Robert Winchester; Andras Perl (Frontiers in Immunology)
IntroductionRheumatoid arthritis (RA) is a systemic autoimmune disease that leads to inflammation of synovial joints and other organs. Many RA patients “share” a common peptide sequence within the HLA-DR (MHC II) molecule expressed on antigen-presenting cells (APC), suggesting that HLA-DR+ cells are important in RA inflammation. We use HLA-DR positivity to comprehensively immunophenotype APC by spectral cytometry.MethodsWe measured mean fluorescence intensities (MFI) of HLA-DR and molecules associated with dendritic cells (CD141, CD1c, CD163, CD11c, CD123, and CD303), monocytes (CD14 and CD16), granulocytic markers (CD15 and CCR3), co-stimulatory molecules (CD86 and CD275), and chemokine receptors (CCR2, CCR3, and CCR7) from RA patients and healthy donors by spectral flow cytometry.ResultsDC2 (CD1c+) showed higher CD86, CD275 (ICOS-L), CD56, and CCR7 in RA (all p < 0.05). CD56 was also increased in (CD163+) DC3 (p = 0.0453). CD15 was increased throughout RA dendritic cell subsets and classical and intermediate monocytes (all p < 0.01). Except for B cells, HLA-DR was not different in RA. A distinct HLA-DR+CD15+CD16+ population appeared in RA (p = 0.0004), which contributed a mean of 1.3% (± SD 2.85%) to the overall HLA-DR+ APC compartment. This HLA-DR+CD15+CD16+ subset was positive for CD83, CD275, and, like plasmacytoid pDC, CD303+. However, in contrast to pDC, it formed distinct t-SNE clusters and differed from reference pDC (CD123+CD303+) by much less CD123 (p < 0.01). The HLA-DR+CD15+CD16+ phenotype correlated with clinical markers of systemic inflammation (p < 0.01).DiscussionIn conclusion, dendritic cell and monocyte alterations in RA include an increased co-stimulatory phenotype of CD1c+ DC2 and CD163+ DC3 with increased CD56 and CD15 in dendritic cells and monocytes. Moreover, the blood of RA patients contains HLA-DR+ cells with shared dendritic cell and granulocytic features. These phenotypic characterizations of RA patients implicate CD1c+ DC2 and CD163+ DC3 in the systemic autoimmune disease rheumatoid arthritis and suggest that increased HLA-DR+ phenotypes with shared granulocytic and dendritic cell features can contribute to RA, potentially by providing enhanced co-stimulatory presentation of self-antigen(s) to CD4+ T lymphocytes.